Análisis financiero de los ingresos y gastos en la empresa Colombatti S.A. durante el periodo 2020 - Llumiguano Guananga, Katherine Sofía (2021)
The present case study that is going to be carried out at the Ferretería Colombatti de Colbapi S.A. on the Financial Analysis of Income and Expenses during the 2020 period, which is dedicated to the wholesale and retail sale of hardware and lock items: hammers, saws, screwdrivers, and other hand tools, accessories and devices; safes, fire extinguishers, located in the city of Babahoyo. The fundamental objective is to analyze how it has affected the income and expenses of the company during the events presented during the aforementioned year, for which some financial reasons will be applied, which are the profit indicators. The methodologies that are applied are deductive and inductive and it is necessary to use exploratory and documentary research, observation and interview with the accountant, in order to reach a reasoning with logical determination and the inductive method in the deductive method. The COVID-19 pandemic during the period of 2020, has affected trade at the national level, in such a way it has been reflected in this case to the hardware store of COLBAPI S.A. on their income and expenses, leaving references in the history of the economic crises that have occurred to the country, due to the circumstances of state of exception trade was paralyzed, given this that the consequences were that their income decreased drastically in order to solve your expenses and costs during the aforementioned year.